Hard X‐ray photoemission study of the covalent‐chain antiferromagnets TlFeS2 and TlFeSe2. Issue 7 (6th May 2013) - Mimura, Kojiro; Motonami, Satoru; Shim, YongGu; Wakita, Kazuki; Jahangirli, Zakir; Alekperov, Oktay; Mamedov, Nazim; Sato, Hitoshi; Utsumi, Yuki; Ueda, Shigenori; Shimada, Kenya; Taguchi, Yukihiro; et al.
Abstract: Bulk electronic structures of covalent‐chain antiferromagnets TlFeS2 and TlFeSe2 have been investigated by hard X‐ray photoemission spectroscopy (HAXPES) and band calculations based on the full‐potential linearized augmented plane wave method. Competition between localized and delocalized characters of Fe 3d electrons has been suggested by the slight discrepancies between valence‐band HAXPES spectra and calculated density of states, as well as Fe 2p spectra with a broad charge‐transfer satellite. It is assumed that this competition closely related to the crystallographic onedimensionality of these materials. (© 2013 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)